Experimental and numerical study on the bending performances of glass FRP molded gratings: Influence of restraining conditions and cover plates. (1st September 2019) - Gattesco, Natalino; Dilena, Michele; Boem, Ingrid
Abstract: The results of experimental bending tests on full-scale, molded FRP (Fiber Reinforced Plastics) gratings are reported and discussed in the paper. In particular, different boundary conditions (perimeter support, two edges support and point support at corners) and the influence of FRP cover applied at one or both sides are investigated and the performances are compared in terms of stiffness and resistance. The collaboration of the ribs in the two directions to the load-carrying capacity clearly emerged in open gratings, which typically collapsed for the tensile failure of the ribs at the mid span. The shear sliding of perimeter ribs was also observed in some cases. The presence of the covers increases both the stiffness and the resistance performances of the samples, however premature failure due to punching shear and cover delamination with buckling occurred. A finite element numerical model was developed to investigate on the stress and strain state of the gratings at both service level and failure: it was validated by comparison with the experimental tests and it is useful for future investigations on more complex configurations.